Reliability of Two Methods of Evaluation of the Apical Limit of Obturation of Root Canals of Primary Teeth: A Pilot Study - Maysa Lannes Duarte; Julia Cocchiarale Pepino; Mariana Coutinho Sancas; Jéssica Pronestino de Lima Moreira; Aline de Almeida Neves; Andréa Vaz Braga Pintor; Laura Guimarães Primo (Association of Support to Oral Health Research (APESB), 2022)
Objective: To verify the concordance in the evaluation of the apical limit of obturation (ALO) in filled root canals of primary teeth between digital and visual methods. Material and Methods: Twenty periapical radiographs of endodontically treated primary teeth were digitalized and evaluated by an endodontics specialist (E1), a PhD pediatric dentist (E2), and a MSc general dentist (E3). Calibrated evaluators (Kappa = 1.00) analysed the images in a light-isolated environment two times (D1 and D2) with a one-week interval between evaluations. ALO scores were categorized as overfilled, flush-filled and underfilled. Results: The intra-rater reliability between methods was 0.82 (D1) and 0.75 (D2) for E1, 0.93 (D1 and D2) for E2, and 0.94 (D1 and D2) for E3. Inter-rater reliability ranged from 0.71 (E1 × E3) and 1.00 (E1 × E2) for the visual method to 0.76 (E1 × E3) and 0.88 (E1 × E2) for the digital method. Spearman correlation coefficients showed a similar ranking among the evaluators. There was greater disagreement among the underfilled and ideal scores. For all evaluators, the digital method favoured the identification of the ideal score. Conclusion: Both methods are suitable for the determination of the ALO of filled primary teeth and can be used in clinical practice.